Differences in health behaviors and health outcomes among non-Hispanic Whites and Arab Americans in a population-based survey in California - Nadia N. Abuelezam; Abdulrahman M. El-Sayed; Sandro Galea (BMC, 2019)
Abstract Background Few population-based studies of Arab American health behaviors and outcomes exist outside of Michigan. We aimed to provide prevalence estimates of health behaviors and outcomes for Arab Americans and compare them to non-Hispanic Whites in California. Methods We used data from the 2003-2016 California Health Interview Surveys. We determined Arab American ethnicity using an algorithm that considered place of birth of the respondent or parent and use of Arabic language at home. Survey-weighted frequencies, chi-squared statistics, and logistic regression analyses were used to compare Arab Americans and non-Hispanic Whites on socioeconomic indicators, health behaviors and health outcomes. Multivariable models were adjusted for age, education level, and insurance status. Results Arab Americans had higher prevalence of no insurance, living below the federal poverty level, and home ownership than non-Hispanic Whites despite high levels of education and low unemployment prevalence. Arab Americans had reduced odds of alcohol consumption (OR: 0.33, 95% CI: 0.24, 0.45), binge drinking (OR: 0.28, 95% CI: 0.19, 0.40), and suicidal ideation (OR: 0.41, 0.25, 0.66) when compared to non-Hispanic Whites in multivariable models. Arab Americans had decreased odds of hypertension (OR: 0.64, 95% CI: 0.50, 0.83) and increased odds of diabetes (OR: 2.03, 95% CI: 1.23, 3.34) when compared to non-Hispanic Whites in multivariable models. Conclusions Arab Americans in California participate in less risky health behaviors and have better health outcomes than non-Hispanic Whites, except with regards to diabetes. Future work aiming to understand the health of Arab Americans should allow for self-identification and less reliance on country of origin and language use at home for sample selection.